Enhancement of foreign gene expression by a dicot intron in rice but not in tobacco is correlated with an increased level of mRNA and an efficient splicing of the intron. - Tanaka, A (1990)
The first intron of castor bean catalase gene, cat-1 was placed in the N-terminal region of the coding sequence of the beta-glucuronidase gene (gusA) and the intron-containing gusA was used with the cauliflower mosaic virus (CaMV) 35S promoter. Using this plasmid, pIG221, the effect of the intron on expression of beta-glucuronidase (GUS) activity was examined in transgenic rice calli and plants (a monocotyledon), and transgenic tobacco plants (a dicotyledon). The intron-containing plasmid increased the level of GUS enzyme activity 10 to 40-fold and 80 to 90-fold compared with the intronless plasmid, pBI221, in transgenic rice protoplasts and transgenic rice tissues, respectively. In contrast, the presence of the intron hardly influenced the expression of the GUS activity in transgenic tobacco plants. Northern blot analysis showed that the catalase intron was efficiently spliced in rice cells while transgenic tobacco plants contained both spliced and unspliced gusA transcripts in equal amounts. Furthermore, the level of the mature gusA transcript in transformed rice calli was greatly increased in the presence of the intron. The catalase intron was removed at the same splice junctions in transgenic rice and tobacco plants. These findings indicate that the stimulating effect of the intron on GUS expression is correlated with an efficient splicing of pre-mRNA and an increased level of mature mRNA.